Unexpected versatile electrical transport behaviors of ferromagnetic nickel films - Zhang, Kai-Xuan; Xu, Hanshu; Keum, Jihoon; Wang, Xiangqi; Liu, Meizhuang; Chen, Zuxin (Journal of physics. Condensed matter, 2024)
Perpendicular magnetic anisotropy (PMA) of magnets is paramount for electrically controlled spintronics due to their intrinsic potentials for higher memory density, scalability, thermal stability and endurance, surpassing an in-plane magnetic anisotropy (IMA). Nickel film is a long-lived fundamental element ferromagnet, yet its electrical transport behavior associated with magnetism has not been comprehensively studied, hindering corresponding spintronic applications exploiting nickel-based compounds. Here, we systematically investigate the highly versatile magnetism and corresponding transport behavior of nickel films. As the thickness reduces within the general thickness regime of a magnet layer for a memory device, the hardness of nickel films’ ferromagnetic loop of anomalous Hall effect increases and then decreases, reflecting the magnetic transitions from IMA to PMA and back to IMA. Additionally, the square ferromagnetic loop changes from a hard to a soft one at rising temperatures, indicating a shift from PMA to IMA. Furthermore, we observe a butterfly magnetoresistance resulting from the anisotropic magnetoresistance effect, which evolves in conjunction with the thickness and temperature-dependent magnetic transformations as a complementary support. Our findings unveil the rich magnetic dynamics and most importantly settle down the most useful guiding information for current-driven spintronic applications based on nickel film: The hysteresis loop is squarest for the ∼8 nm-thick nickel film, of highest hardness with R xy r / R xy s ∼ 1 and minimum H s − H c , up to 125 K; otherwise, extra care should be taken for a different thickness or at a higher temperature.